A multifunctional bioconjugate module for versatile photoaffinity labeling and click chemistry of RNA - Kaiser, Stefanie; Seidu-Larry, Salifu; Burhenne, Jürgen; Motorin, Yuri; Helm, Mark (Nucleic acids research, 2011)
A multifunctional reagent based on a coumarin scaffold was developed for derivatization of naive RNA. The alkylating agent N3BC [7-azido-4-(bromomethyl)coumarin], obtained by Pechmann condensation, is selective for uridine. N3BC and its RNA conjugates are pre-fluorophores which permits controlled modular and stepwise RNA derivatization. The success of RNA alkylation by N3BC can be monitored by photolysis of the azido moiety, which generates a coumarin fluorophore that can be excited with UV light of 320 nm. The azidocoumarin-modified RNA can be flexibly employed in structure-function studies. Versatile applications include direct use in photo-crosslinking studies to cognate proteins, as demonstrated with tRNA and RNA fragments from the MS2 phage and the HIV genome. Alternatively, the azide function can be used for further derivatization by click-chemistry. This allows e.g. the introduction of an additional fluorophore for excitation with visible light.